New episodes of depression among Medicare beneficiaries with chronic obstructive pulmonary disease. (18th August 2015) - Albrecht, Jennifer S.; Huang, Ting‐Ying; Park, Yujin; Langenberg, Patricia; Harris, Ilene; Netzer, Giora; Lehmann, Susan W.; Khokhar, Bilal; Simoni‐Wastila, Linda
Abstract : Objectives: Depression is a common comorbidity of chronic obstructive pulmonary disease (COPD) and is associated with increased exacerbations, healthcare utilization, and mortality. Among Medicare beneficiaries newly diagnosed with COPD, the objectives of this study were to (1) estimate the rate of new episodes of depression and (2) identify factors associated with depression. Methods: We identified beneficiaries with a first diagnosis of COPD during 2006–2012 using a 5% random sample of Medicare administrative claims data by searching for ICD‐9‐CM codes 490, 491.x, 492.x, 494.x, or 496. We identified episodes of depression using ICD‐9‐CM codes 296.2x, 296.3x, and 311.xx. We calculated incidence rates and their 95% confidence intervals (95% CI) and used a discrete time analysis to identify factors associated with development of depression. Results: Between 2006 and 2012, 125, 348 beneficiaries meeting inclusion criteria were newly diagnosed with COPD. Twenty‐three percent developed depression following COPD diagnosis. The annualized incidence rate of depression per 100 beneficiaries following COPD diagnosis was 9.4 (95% CI 9.3, 9.5). Rates were highest in the first 2 months following COPD diagnosis. COPD diagnosis was associated with increased risk of depression (risk ratio 1.76; 95% CI 1.73, 1.79) as were COPD‐related hospitalizations (risk ratio 4.59; 95% CI 4.09, 5.15), a measure of COPD severity. Conclusions: Diagnosis of COPD increases the risk of depression. This study will aid in the allocation of resources to monitor and provide support for individuals with COPD at high risk of developing depression. Copyright © 2015 John Wiley & Sons, Ltd.